FREE SCHOOL DI JEPANG DALAM KOMIK MICHIKUSA KYOUSHITSU KARYA MARIKO NAGAHARA - Nova Sarastini, Putu (Humanis; Volume 11. No2. Mei 2015)
The social problems with students in Japan such as ijime, futoukou, and the others problem are often used as a theme in literature works like novels or comics. Michikusa Kyoushitsu comic is one of Japanese literature works which has the theme of student social problems in Japan. Michikusa Kyoushitsu comic also tells about free school that has became one of the solutions in social problem students in Japan. According to the result of analysis, it can be known about free school, it’s background of free school, education system of free school, and the other event which happening at free school, and the society opinion about free school in Japan. It can also be learnt about social interaction of students at free school in the relation of miuchi and nakama.
Keywords: free school, social interaction, futoukou